FAKTOR-FAKTOR YANG MEMENGARUHI DIVIDEND POLICY - LEONY, LEONY; BENY, BENY (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
The objective of this research is to empirically test and analyze the impact of managerial ownership, debt policy, return on asset, firm size, and free cash flow on dividend policy. This study also aims to confirm the consistency of the current research findings with previous studies. The research focuses on companies listed in the consumer non-cyclicals sector on the Indonesia Stock Exchange (IDX) during the period from 2012 to 2022. Purposive sampling method is utilized to select 10 companies that meet three criteria, and the panel data regression technique is applied to analyze the sample. The results of this research indicate that the variables of managerial ownership, return on asset, and firm size significantly influence dividend policy, while debt policy and free cash flow do not significantly influence dividend policy.